Leading Six Sigma: A Step-by-Step Guide Based on Experience with GE and Other Six Sigma Companies - Snee, Ronald; Hoerl, Roger (Financial Times Prentice Hall books., 2002)
Leading Six Sigma is the complete guide to leading quality initiatives in your company. Top Six Sigma consultant Ronald Snee and GE quality leader Roger Hoerl demonstrate how to deploy a Six Sigma plan that reflects your unique organization, and key lessons learned from the world's best implementations. Coverage includes every facet of Six Sigma leadership: strategy, goal setting, metrics, training, roles/responsibilities, processes, reporting, rewards, ongoing review, and much more.